Gestão da manutenção: análise da criticidade em equipamentos de uma indústria no sudoeste do Paraná - Michelon, Éden Carlos (2019)
The constantly evolving industry increasingly seeks to transform its processes and make them more efficient, using equipment with the most advanced technology in order to ensure the expected quality. Within this context, industrial maintenance is evidenced as an important piece for companies seeking to reach their goals in the competitive market. In order for the maintenance sector to achieve the results expected by corporations, with the planning and use of the best available tools and resources, the criticality analysis matrix enables visualization and assists maintenance management in their decision making. The present work of criticality analysis is one of the processes of the reliability centered maintenance tool, aiming at reducing the maintenance cost and the occurrence of process stoppages due to inefficient maintenance. Therefore, the purpose of this work is the implementation of the criticality matrix in a production line of a cement artifact manufacturing company in order to increase process reliability and reduce maintenance costs. The survey conducted by the company studied defined a specific production line within its production units, using the indicators already established by the production, quality and work safety sector, which were related to the constraints of the criticality analysis matrix. It has been shown that in 46% of the equipment, the maintenance technique to be used in order to reduce costs and increase maintenance reliability must be preventive maintenance.